Dos objetos de bronce de época visigoda en el yacimiento de Begastri (Cehegín, Murcia). Estudio y restauración - Vallalta Martínez, Pilar (Antigüedad y Cristianismo, 1998)
At the excavation in Begastri in September 1988 a carved bronze "lily-shaped" buckle was discovered with a bronze bowl which has vaious metal plates riveted to the side. A study reveals that these are from about the end of the seventh or the beginning of the eighth centuries AD. The restoration of the two bronzes consisted of both manual and machine assisted cleaning, desaltification and inhibition; finally they were given a protective coating.